2004
DOI: 10.1007/s00359-004-0526-3
|View full text |Cite
|
Sign up to set email alerts
|

Venom effects on monoaminergic systems

Abstract: The monoamines, dopamine, epinephrine, histamine, norepinephrine, octopamine, serotonin and tyramine serve many functions in animals. Many different venoms have evolved to manipulate monoaminergic systems via a variety of cellular mechanisms, for both offensive and defensive purposes. One common function of monoamines present in venoms is to produce pain. Some monoamines in venoms cause immobilizing hyperexcitation which precedes venom-induced paralysis or hypokinesia. A common function of venom components tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 79 publications
2
25
0
Order By: Relevance
“…Although MCs have long been thought to promote morbidity and mortality following snake bites and envenomations by other animals (Dutta and Narayanan, 1952;Weisel-Eichler and Libersat, 2004), we have found that in contrast, MCs enhance the resistance against certain venoms (Metz et al, 2006b). Surprisingly, envenomation of the skin with venom from the Western Diamondback rattlesnake induces significantly larger hemorrhagic lesions in MC-deficient Kit W-sh /Kit W-sh than in wildtype mice or in mice that were selectively repaired of their MC-deficiency in the skin.…”
Section: Skin Mast Cells Sense and React To Immediate Dangermentioning
confidence: 94%
“…Although MCs have long been thought to promote morbidity and mortality following snake bites and envenomations by other animals (Dutta and Narayanan, 1952;Weisel-Eichler and Libersat, 2004), we have found that in contrast, MCs enhance the resistance against certain venoms (Metz et al, 2006b). Surprisingly, envenomation of the skin with venom from the Western Diamondback rattlesnake induces significantly larger hemorrhagic lesions in MC-deficient Kit W-sh /Kit W-sh than in wildtype mice or in mice that were selectively repaired of their MC-deficiency in the skin.…”
Section: Skin Mast Cells Sense and React To Immediate Dangermentioning
confidence: 94%
“…Indeed, MC-deficient mice were found to be 10-fold more susceptible to the deadly effects of the venom than wildtype mice, and MC-derived carboxypeptidase A was proven to be responsible for enhancing the resistance against the venomous effects [21]. MCs have long been thought to promote the pathology following snake bites, for example by releasing vasoactive mediators such as histamine, which can increase vascular permeability, facilitate both local tissue swelling and the systemic distribution of the venom, and increase its overall toxicity [51,52]. The finding that MCs instead elicit a protective innate response resulting in enhanced resistance to the venom of A. engaddensis was, therefore, unexpected.…”
Section: Effector Functions Of Mast Cell-derived Proteasesmentioning
confidence: 99%
“…Venoms derived from several animal species other than reptiles and honeybees, including those from scorpions (32), also have been shown to activate mast cells. We therefore also tested venoms from 2 species of medically important scorpions, the deathstalker (yellow) scorpion (Leiurus quinquestriatus hebraeus) (33)(34)(35) and the Arizona bark scorpion (Centruroides exilicauda) (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%